2020
DOI: 10.1210/clinem/dgaa456
|View full text |Cite
|
Sign up to set email alerts
|

Letter to the Editor from Valdes-Socin et al: “Genetic Study in a Large Cohort Supported Different Pathogenesis of Graves’ Disease and Hashimoto’s Hypothyroidism”

Abstract: Objective: The conversion of Hashimoto's thyroiditis (HT) to hyperthyroidism due to thyrotropin receptor antibodies is intriguing and considered rare. The contribution of TSH receptor blocking antibodies (TRAb), which may be stimulators (TSAb) or blockers (TBAb), is suspected. We describe clinical and biological variables in a series of patients switching from Hashimoto's thyroiditis to Grave's disease. Subjects and methods: Retrospective case study of 24 patients with Hashimoto's thyroiditis followed during 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The mechanism of H. pylori -induced Vit. B12 deficiency could be related to the failure of gastric parietal cells to produce intrinsic factor in patients with H. pylori-associated corpus-predominant chronic gastritis [26] .…”
Section: When To Search For H Pylori Infection?mentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of H. pylori -induced Vit. B12 deficiency could be related to the failure of gastric parietal cells to produce intrinsic factor in patients with H. pylori-associated corpus-predominant chronic gastritis [26] .…”
Section: When To Search For H Pylori Infection?mentioning
confidence: 99%
“…Primary immune thrombocytopenia (ITP) is an autoimmune disorder, linked to H. pylori infection [26] . The putative pathogenic mechanism of this association is a molecular mimicry between platelet surface glycoproteins and amino acid sequences of H. pylori virulence factors, such as H. pylori lipopolysaccharide (LPS), Vac A , CagA , and urease B [25 , 27] .…”
Section: When To Search For H Pylori Infection?mentioning
confidence: 99%
“…Although he additionally postulated that the kidneys are its pharmacological target, it was not until the 1970s that inhibition of renal tubular glucose reabsorption was specified as the mechanism of action of phlorizin [16], while Rosetti et al demonstrated an amelioration of insulin resistance and hyperglycemia after phlorizin administration in 1987 [17]. The development of the first orally absorbable, phlorizin-derived SGLT-1 and -2-inhibitor was followed by a rapid discovery of more orally active agents and in 2013, canagliflozin was the first SGLT2-inhibitors that received Food and Drug Administration (FDA) approval for the treatment of type 2 diabetes, followed by Dapagliflozin and Empagliflozin in 2014 [18]. SGLT co-transporters are subdivided into two categories: SGLT-1 and SGLT-2 co-transporters.…”
Section: Mechanisms Of Action Of Sglt-2 Inhibitorsmentioning
confidence: 99%